The Role of Islamic Boarding School Leaders in Managing Learning - Ali Mumin Budiman; Nanang Naisabur; Silmi Amrullah; Dina Kamila Syarifa (al-Afkar, Journal For Islamic Studies, 2024)
The role of a leader and his ability to manage an institution are benchmarks for the success of that institution. This research aims to analyze the extent of involvement of Islamic boarding school leaders in managing learning. In detail, the researcher wants to describe the role of Islamic boarding school leaders in planning learning, implementing learning and their role in coordinating and evaluating post-learning processes. The reason the researcher raised this theme was based on the fact that an Islamic boarding school leader has busier activities outside the Islamic boarding school environment, than within his own Islamic boarding school environment. So that the management of the institution is entrusted to subordinates. The research method used is descriptive qualitative research. The data collection techniques are through interviews, observation and documentation studies. The collected research data is then analyzed by reviewing all the data obtained in the field and arranged in a more systematic manner. The results of the research show that Islamic boarding school leaders have carried out their role as fully as possible in managing learning in accordance with the leadership's functions and duties which are based on functions in management.